Ganadería y deforestación en América Latina Tropical: Qué podemos hacer? - Rivas Ríos, Libardo (International Center for Tropical Agriculture, 1998)
Short-term trends show that livestock production is becoming an increasingly important factor in regional development, possibly because of the combined effect of increasing the forages on offer and planting crops better adapted to the environmental and economic conditions of marginal areas and the decreasing interest of the State in expanding the agricultural frontier. Overall planning of land use should be improved, but to do so, a more detailed characterization and monitoring of deforestation are essential. Causes and effects of deforestation should be identified and quantified, as well as the magnitude and location of high-risk areas and the urgency of measures required to confine the process. Several ongoing projects aim to demonstrate the technical and economic viability of carbon sequestration by replacing slash-and-burn agriculture with activities such as timber production in developing countries and the possibility of marketing these services in global environmental markets. This opens new possibilities for more sustainable land use, without reducing the standard of living of the population. The present work was based on a broad literature review and covers the following topics: (a) deforestation, (b) factors determining deforestation, (c) livestock expansion and deforestation, and (d) economic policies and technology. Conclusions are also provided.